G220 Changing patterns of growth in prader-willi syndrome. (12th March 2018) - Neophytou, GI; Frixou, M; Shaikh, MG; Kyriakou, A
Abstract : Introduction/aim: Children with Prader-Willi syndrome (PWS) show alterations in infantile, childhood and pubertal growth. Growth Hormone (GH) therapy is recommended due to reported improvements in height velocity (HV) and body composition. The aim was to describe the patterns of growth in PWS and the influence of both changes in clinical practice and GH therapy. Methods: Height SDS(HSDS), BMISDS and HVSDS of children attending a dedicated PWS clinic, 2000–2017, were analysed. To identify changes in growth we compared growth parameters between 2000–2012 and 2013–2017. In 21 children who received GH(median age at GH start 4.92 years (2.27, 8.1)), consecutive measurements were available at −1, 0, +1 and+2 years from GH start. Results: Overall, 60 children(31 F/29 M) were included. Three phases of growth after the age of 1 year were identified: 1–5 years, with acceleration in both HSDS(r, 0.310, p, <0.0001) and BMISDS(r, 0.602, p, <0.0001); 6–12 years, with stabilisation in both HSDS(r, 0.063, p, 0.417) and BMISDS(r, −0.154, p, 0.087); and 13–18 years, with deceleration in HSDS(r, −0.383, p, <0.0001) and unchanged BMISDS(r, 0.015, p, 0.896). At age 5, children in 2013–2017 (n, 12) had higher HSDS [median, −0.08 (-1.74, 1.54) vs −1.04(−4.16, 0.5)] than those in 2000–2012 (n, 18) (p, 0.03). At age 12, children in 2013–2017 (n, 5) had higher HSDS [median, 1.13 (-0.62, 1.59) vs −1.35 (-4.27, 0.23)] (p, 0.027) and lower BMISDS [median, 1.05 (-0.13, 2.14) vs 2.44 (0.13, 4.3)] (p, 0.032) than those in 2000–2012 (n, 11). After 2 years on GH, median HSDS improved from −1.43 (-4.59, 0.95) to −0.11(−3.53, 1.57) (p, <0.0001) and median HVSDS from 0.62 (-5.9, 4.17) to 2.8(−2.2, 5.2) (p, 0.027). BMISDS was unchanged (Table 1). Conclusion: We were able to delineate 3 distinct phases of growth in PWS. Changes in our clinical practice have led to improvements in both height and BMI. GH therapy was associated with an increase in height and stabilisation of BMI.